Learning environment for Secondary 3 Elementary Mathematics - T. Apirame (2017)
Technology in education is a broad topic which is often discussed nowadays. Many educational institutions are moving towards technology-based learning curriculum. This project explores various methods to develop an interactive online learning site for Secondary Three Elementary Mathematics (E-Math), which will motivate students to do better in the subject and serve as a supplementary tool of learning. Moodle is used in the project as the base environment to design the interactive learning portal with lessons, quizzes, assignments and interactive learning tools.